Rumah RUMAH TUMBUH SEBAGAI SOLUSI BAGI MBR : DESA KEDUNGPRING KECAMATAN KEMRANJEN KABUPATEN BANYUMAS - Dwi Jati Lestariningsih Ning; Wahyu Dwi Yudono; Ary Sismiani (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Residential homes are dynamic in nature, capable of changing or expanding over time. Some of the factors influencing the expansion of homes in Kedungpring Village, Kemranjen Sub-district, Banyumas Regency, include: an increase in family size and an increase in activities (such as running a small shop, sewing, or other businesses) that require additional space. The problem faced by low-income communities (MBR) is the expansion of homes without proper planning. This can pose risks to the building’s structure, spatial layout or lead to inefficient costs. Designing a ‘growing home’ from the outset can be a solution to these problems. The methods used in this activity include outreach sessions and interactive discussions. The awareness-raising sessions aim to enhance the community’s understanding of the ‘growing home’ concept as a solution for phased house construction in line with a family’s economic capacity. The outcomes of this initiative include: the community understanding the stages of ‘growing home’ construction; and, by understanding the basic structure of the home, being able to develop safer homes. With regard to the utilisation of natural resources and health, it is hoped that community awareness will grow regarding the importance of natural lighting and ventilation in residential homes.